2013
DOI: 10.1371/journal.pone.0067597
|View full text |Cite
|
Sign up to set email alerts
|

A Proline-Hinge Alters the Characteristics of the Amphipathic α-helical AMPs

Abstract: HP (2–20) is a 19-aa, amphipathic, α-helical peptide with antimicrobial properties that was derived from the N-terminus of Helicobacter pylori ribosomal protein L1. We previously showed that increasing the net hydrophobicity of HP (2–20) by substituting Trp for Gln17 and Asp19 (Anal 3) increased the peptide's antimicrobial activity. In hydrophobic medium, Anal 3 forms an amphipathic structure consisting of an N-terminal random coil region (residues 2–5) and an extended helical region (residues 6–20). To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 35 publications
(40 reference statements)
1
36
0
Order By: Relevance
“…However, in this family of peptides, we only need to analyze up to the proline residue, since this residue would act as a hinge if the α-helix were to extend throughout all the residues. [55] As observed in Figure 8, the VIH and GGH derivatives have five hydrophobic residues on one side of the helix, whereas the DAH derivative has only four. The parent peptide, sh -buforin, has only three hydrophobic residues (not shown).…”
Section: Discussionmentioning
confidence: 98%
“…However, in this family of peptides, we only need to analyze up to the proline residue, since this residue would act as a hinge if the α-helix were to extend throughout all the residues. [55] As observed in Figure 8, the VIH and GGH derivatives have five hydrophobic residues on one side of the helix, whereas the DAH derivative has only four. The parent peptide, sh -buforin, has only three hydrophobic residues (not shown).…”
Section: Discussionmentioning
confidence: 98%
“…FACS analysis showed that Hp1404 damaged membranes while Hp1404-T1e did not. Based on these results, we investigated the potential presence of intracellular peptide targets using the DNA binding assay 50 . Surprisingly, Hp1404-T1d and Hp1404-T1e interacted with DNA, suggesting that their differences with the parent peptide may imply the existence of a distinct action mechanism 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The prokaryotic selectivity of the peptides to mammalian cells was determined by measuring their hemolytic activity toward hRBCs, as described previously in our study (Table 1) [41].…”
Section: Resultsmentioning
confidence: 99%